Baseline manipulation in voluntary carbon offset programs. (December 2017) - Liu, Xiaoyu; Cui, Qingbin
Abstract: Studies of voluntary carbon trading almost exclusively assume the additionality baselines are set by regulators who have either entirely perfect or imperfect information about the costs and emissions of projects. In practice, regulators are often less informed than project proponents; therefore, the baselines are more likely to be privately defined even for sectoral crediting. The primary concern with privately defined baselines is that baseline developers may exert their powers to manipulate the baselines, leading to increases in sectoral emission caps. This study models baseline manipulation behaviors in the context of adverse selection, where participants can self-select into the market. The theoretical results show that the extent to which the baseline is manipulated is highly dependent on who is assigned as the baseline developer. The more the baseline developer emits, the more likely the developer manipulates the baseline. The results are then further discussed in the context of the U.S. commercial building sector, where empirical methods are introduced to characterize cost and revenue functions. The empirical analysis reveals that, because of the notably low price elasticity of the offset supply, baselines are often positively biased even with third-party verifications. If that policymakers wish to allow baselines to be privately defined, they might be advised to implement baseline setting on an invitation-only basis to specific emitters that have relatively lower historical emissions. Highlights: This study models baseline manipulation behaviors in voluntary carbon offset programs. The degree of manipulation is highly affected by the baseline developer's emission level. The baselines for the building sector are often biased even with third-party verification. The biased baselines can result in 700 million metric tons of carbon leakage each year. Policymakers are advised to invite low emitters to be the baseline developers.